Aplikasi Penggunaan Serah Wangi Sebagai Bioaditif Alami untuk Karakterasi Unjuk Kerja dari Mesin Diesel - Abdul Muhyi; Rico Aditia Prahmana; Devia G. C. Alfian; Dicky J. Silitonga; Didik Supriyadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
The consumption of diesel fuel in Indonesia is increasing every year, one way to overcome this problem is to use natural bioaditive in the form of essential oils found in Indonesia. Essential oils used in this study are fragrant lemongrass because fragrant lemongrass contains carboxylic compounds (-COOH) [1,2,3]. With the aim of improving engine performance and reducing fuel consumption. This research was conducted by mixing fragrant citronella oil with diesel oil with a percentage of 1%, 0.5% and 0.1% of the total volume. Diesel engines are operated with variations in loading 200, 400, 600, 800, 1000, 1200, 1400, 1600, 1800 and 2000 W at a constant engine speed of 1500 rpm. The variables measured and calculated in this experiment are power, torque, Break Mean Effective Pressure (BMEP), Specific Fuel Consumption (SFC). The results showed that adding citronella oil to diesel fuel with a percentage of 1%, 0.5% and 0.1% significantly reduced fuel consumption by 15.5%, 3.6% and 2.6% respectively. The maximum reduction in fuel consumption reaches 0.055 liters / hour at 200W loading with a bioaditive level of 0.1%. The next study planned is to mix clove oil and citronella oil as bioaditive so that it is expected to reduce fuel consumption and engine corrosion. Keywords: Diesel engine, bioaditive, fragrant citronella oil, performance of diesel engines, fuel consumption